Analysis and spatial mapping of antimicrobial prescription completeness and legibility in a public community pharmacy - Friedemann BERGER; Fabrícia Benda OLIVEIRA; Sérgio Henriques SARAIVA; Ariadne Marra SOUZA; Carlos Henrique OLIVEIRA; Larissa COUTO-ROSA; Genival Araujo SANTOS-JÚNIOR (Revista Brasileira de Farmácia Hospitalar e Serviços de Saúde)
Objective The phenomenon of resistance of antimicrobials is associated with inappropriate use. The analysis of antimicrobial prescriptions, evaluating their legibility and completeness, is interesting because it aims to identify possible errors that may compromise the proper use. This study aims to evaluate the completeness and legibility of antimicrobial prescriptions in a municipality in southeastern Brazil. Methods The antimicrobial prescriptions retained at the Community Pharmacy in the municipality of Alegre, from March 2018 to February 2019, underwent a simple random sampling process to obtain the sample for analysis. In addition, data on the origin of the prescription were georeferenced, generating a map correlating the evaluation of the legibility of the prescriptions with the health units of the municipality. This study was approved by the Research Ethics Committee of the Administrative Coordination of Southern Espírito Santo (CASES) with the CAAE number: 13586319.6.0000.8151. Results The sample comprised 359 prescriptions containing 373 antimicrobials. The majority of prescriptions (97.2%) contained complete data from the prescribing professional, and 70.2% presented the patient’s identification without abbreviations, although 44% showed legibility problems in this parameter. In 35.4% of the prescriptions, there were legibility problems and no data in the joint evaluation of the prescribed antimicrobial, concentration, quantity, pharmaceutical form, dose, frequency, and duration of treatment. In the evaluation of the posology (dose and frequency) and duration of treatment, complete data were found in 82.3% and 71.8%, respectively. Most of the antimicrobials prescribed, 95.4% and 93% respectively, were listed in the National List of Essential Medicines (Rename) and were in the Brazilian Common Denomination (DCB) format. The most prescribed antimicrobial was Cephalexin 500mg. Conclusion The study indicated the presence of antimicrobial prescriptions that do not comply with legislation and may compromise patient safety. These findings highlight the need for targeted interventions to improve prescription legibility and adherence to the regulatory standards in public health settings.